Lightning impulse breakdown performances of palm oil and coconut oil under non-uniform field - Thien, Yee Von (2016)
Nowadays transformers have become essential for the electricity transmission and distribution network since the invention of transformers in late 1800s. The oil filled types transformer is commonly used and petroleum based MO has been widely used as transformer dielectric insulation fluid for decades. However, the usage of MO has several drawbacks such as non-biodegradable, low flash and fire points and could contaminate the soil and waterways if serious spill occurs. Recently, vegetable oil is introduced as the potential candidate, since it is biodegradable, non-toxic and has better environmental performance with high flash and fire points. The seed based natural ester has been applied successfully as dielectric insulation fluid in small and medium transformers. In Malaysia, due to the huge plantation of PO, the types of vegetable oils considered for transformer applications are PO and CO. Before these oils can be applied in transformers, extensive assessment on its performance need to be carried out since the in-service failure could be costly. Among the common assessment is the lightning impulse strength, which is one of the important parameter for insulation design of a transformer. This work presents the experimental studies on the lightning impulse breakdown voltages of PO and CO under various gap distances. Three different variations of PO and one sample of CO were considered in all tests. The lightning breakdown voltage test was carried out under non-uniform electric field configuration where the gap distances were set in the range of 2-25 mm. Three testing methods which are rising voltage, up-and-down and multiple-level were used to determine the breakdown voltage results. The lightning breakdown voltages performances of PO and CO compared with MO were analysed. All lightning breakdown voltages were analysed and the withstand voltages were evaluated through Weibull distribution. It was revealed that there is a bright future possibility of using PO as alternative insulation fluids in transformers where the breakdown voltages performances of PO and CO are comparable with MO under positive lightning impulse. However, the negative lightning impulse breakdown voltage of MO is found to be higher than both PO and CO, which might due to their different chemical structural. Based on this study, the lightning breakdown strengths of PO and CO at I% and 50% breakdown probability can be acquired through the empirical formulas produced where the breakdown voltage at large gap distances can be predicted which are important for transformers insulation design. The knowledge of the lightning impulse characteristics of PO and CO are obtained and can be used for further improvement in future works.